Internet connectivity disruption in United Kingdom (United Kingdom) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in United Kingdom. Data sourced from IODA.
Network Disruption Incident ID: GB-2026-0013. Severity: critical. Confidence: 67%